Annotated bird sighting list for Spring 1994 compiled by James Scheib - Scheib, Jameset al (1994)
An annotated list of birds sighted by James Scheib. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of Spring 1994. Plustek - flatbed